Energy efficiency in EU universities – results of the 1st level audit - Kęstutis Valančius; Rūta Mikučionienė (Mokslas: Lietuvos Ateitis, 2010)
The paper presents the main ideas of the project considering the programme “Intelligent Energy – Europe (IEE) / Use Efficiency: Universities and Students for Energy Efficiency”. The article focuses on project goals, outputs, results and work programme. The methods of energy performance analysis and consumption benchmarks are described. Operational Rating method for 1st level analysis is preferred as the most reasonable. The principles of critical buildings, including some examples are identified. The obtained results of the 1st level audit of 9 EU universities are given.